Dose- and time-dependent manners of moxifloxacin induced liver injury by targeted metabolomics study - Hu, Ting; Sun, Yuan; An, Zhuoling (Frontiers in Pharmacology, 2022)
Moxifloxacin is the most widely prescribed antibiotics due to its excellent oral bioavailability and broad-spectrum antibacterial effect. Despite of its popularity, the rare and severe liver injury induced by moxifloxacin is a big concern that cannot be ignored in clinical practice. However, the early warning and related metabolic disturbances of moxifloxacin induced hepatoxicity were rarely reported. In this study, the dose- and time-dependent manners of moxifloxacin induced liver injury were investigated by a targeted metabolomics method. In dose-dependent experiment, three different dosages of moxifloxacin were administered to the rats, including 36 mg kg−1 d−1, 72 mg kg−1 d−1, and 108 mg kg−1 d−1. In time-dependent experiment, moxifloxacin was orally administered to the rats for 3, 7 or 14 consecutive days. Pathological analysis showed that moxifloxacin caused obvious transient hepatotoxicity, with the most serious liver injury occurred in the 7 days continuous administration group. The transient liver injury can be automatically restored over time. Serum levels of liver function related biochemical indicators, including ALT, AST, TBIL, ALP, SOD, and MDA, were also measured for the evaluation of liver injury. However, these indicators can hardly be used for the early warning of hepatotoxicity caused by moxifloxacin due to their limited sensitivity and significant hysteresis. Targeted metabolomics study demonstrated that serum concentrations of fatty acyl carnitines, fatty acids and dehydroepiandrosterone can change dynamically with the severity of moxifloxacin related liver injury. The elevated serum levels of fatty acyl carnitine, fatty acid and dehydroepiandrosterone were promising in predicting the hepatotoxicity induced by moxifloxacin.